The Jurisdiction Of Establishing Parties In Islam - Yousef Attia Hasan Klaibe (My University, 2011)
This study aims at demonstrating the legitimacy of political parties in the Islamic state, and reviewing the words in the judgment on this issue supported by evidence, these words focused on three trends: Inhibitors by no means, those who permit within the Islamic rules, and those who permit by no means. I divided this research into an introduction, four chapters and a conclusion. The first chapter demonstrates the concept and the fact of parties and their relationship with some other concepts, the second chapter deals with the historical emergence of political parties, and the third chapter reviews the three statements concerning judgment of the establishment of political parties in Islam, accompanied by the evidences which will be discussed later, and in the fourth and final chapter I displayed the intended aim of the parties concerning the issue and the strong opinion. In the conclusion, I showed the most important findings of the study, which can be summarized in the legalization of political parties in various forms as long as they respect the Constitution of the Nation of Islam taking into consideration that the external debater, D. Mohammad Metlaq Assaf, has reserved on this opinion.

تهدف هذه الدراسة لبيان مدى مشروعية الأحزاب السياسية في الدولة الإسلامية، واستعراض الأقوال في حكم هذه المسألة مع بيان الأدلة، حيث تمحورت هذه الأقوال بثلاثة اتجاهات المانعون بإطلاق، والمبيحون ضمن الأصول الإسلامية، والمبيحون بإطلاق. وقد انتظم عقد هذا البحث في مقدمة وأربعة فصول وخاتمة، فجعلت الفصل الأول لبيان مفهوم الأحزاب وحقيقتها وعلاقتها مع بعض المفاهيم الأخرى، وتناول الفصل الثاني النشأة التاريخية للأحزاب السياسية، والفصل الثالث لاستعراض الأقوال الثلاث في حكم إقامة الأحزاب السياسية في الإسلام مصحوبة بالأدلة ومناقشتها، وأما الفصل الرابع والأخير فعرضت فيه رأي الدراسة في المسألة والترجيح، وبينت النظرة المقاصدية للأحزاب. وختمت البحث بخاتمة بينت فيها أهم النتائج التي توصلت إليها الدراسة، والتي يمكن إجمالها في إباحة الأحزاب بشتى أشكالها ومسمياتها، ما دامت تحترم الدستور العام للدولة الإسلامية، هذا مع العلم بأن المناقش الخارجي د. محمد مطلق عساف قد تحفظ على هذا الترجيح.
حكم إقامة الأحزاب في الإسلام